The Psychosocial Impact of Modifying Face and Body Photographs in Social Media (Journal of Advanced Research in Social Sciences, 2020)
Social media usage has become widespread in the past decade, and studying its far-reaching impacts requires an interdisciplinary approach. This pilot study takes the first step in discovering the psychosocial impact of specific media content, modified face and body photographs, and the act of modifying in this context with a mixed-method assessment. The analysis is based on structured interviews with ten social media users with various demographic traits (such as gender, age, or education) who were presented eight pairs of "before-and-after modification" photographs and completed the Beck Depression Inventory (BDI) to assess a possible relationship between modified face and body photographs in social media and depression. All the participants encountered such face and body photographs that they considered "modified". The definition of modification was "retouching, editing, using filters or any kind of digital altering mechanism". Seventy per cent of users admitted that they took the opportunity to modify photographs of their face and body. The average Beck score of the image modifiers was 7.14, while non-modifiers' was 2.33. Thirty per cent of the interviewees probably had mild depression or were in a mildly depressive state during the data collection based on their Beck scores; all were image modifiers exposed to modified pictures. Besides the fully structured interviews with social media users, half-structured interviews were also recorded with four experts – a social psychologist, a clinical psychologist, a plastic surgeon, and a professional photographer – to gain a deeper understanding of this complex topic and contribute to further, more extensive research on this area.